Evaluierung der Strafvorschriften zur Bekämpfung des Menschenhandels (§§ 232 bis 233a StGB) - Bartsch, Tillmann (Interdisziplinäre Beiträge zur Kriminologischen Forschung, 2022)
The present study, commissioned by the Federal Ministry of Justice and Consumer Protection, critically examined the criminal law provisions on combating human trafficking (Sections 232 to 233a of the Criminal Code), which were reformed in 2016. For this purpose, among other things, a file analysis, numerous interviews with experts and a workshop were conducted. The result of the research is sobering: The goals pursued by the legislator with the reform were not achieved for the most part. The authors therefore propose several measures to improve the fight against human trafficking.